Correlation of Serum BACE1 With Emergence Delirium in Postoperative Patients: A Preliminary Study - Ye, Chunyan; Zhang, Yanrong; Luo, Sumei; Cao, Yanan; Gao, Feng; Wang, E. (Frontiers in Aging Neuroscience, 2020)
Background: The mechanism underlying delirium, a common acute fluctuating mental state, may be related to the activation of a neuroinflammatory response. In this study, we attempted to investigate whether plasma inflammatory response markers, vascular and cerebrovascular injury-related markers, and neurodegeneration-associated markers were associated with emergence delirium (ED). Methods: Patients aged 50 years or above who underwent elective laparoscopic surgery under general anesthesia were included in this study. Delirium was assessed postoperatively with the Richmond Agitation Sedation Scale (RASS) and the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) scale. Plasma samples were collected from ED patients and non-ED patients to test concentrations of inflammation markers, including interleukin 6 (IL-6), chitinase 3-like 1 (CHI3L1), S100 calciumbinding protein B (S100B), lipoprotein-associated phospholipase-A2 (Lp-PLA2), and macrophage migration inhibitory factor (MIF);vascular and cerebrovascular injury-related markers, including intercellular cell adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule (VCAM‐1); and neurodegeneration-associated markers, including alpha‐synuclein (α‐Syn) and β‐secretase 1 (BACE1).Binary logistic regression analysis was performed to analyze the relationship between biomarkers and ED, and receiver operating characteristic (ROC) curves were used to analyze the diagnostic value of biomarkers. Results: A total of 104 patients were included in this study, with an average age of 63.69±7.21. IL-6 (OR=2.73, 95% CI: 1.66-6.44, P=0.022), S100B (OR=4.74, 95% CI: 1.88-11.95, P=0.001) and BACE1 (OR=6.54, 95% CI: 2.57-16.65, P<0.000) were independent biological indicators for the occurrence of ED.CHI3L1, Lp-PLA2, MIF, ICAM-1, VCAM-1, and α-Syn were unrelated to ED. Plasma BACE1 level had a possible diagnostic value for ED (area under curve [AUC]=0.75, 95% CI: 0.66-0.85), whereas plasma IL-6 (AUC=0.62, 95% CI: 0.51-0.73) and S100B (AUC=0.65, 95% CI: 0.54-0.76) levels had little diagnostic value for distinguish ED versus non-ED. Conclusion: Higher levels of systemic inflammation marker IL-6, cerebral inflammation marker S100B, and neurodegeneration-associated marker BACE1 are related to ED. Plasma BACE1 may be a potential diagnostic biomarker for ED.